An Unusual Case of Accidental Hanging by Cloth (Shawl) Entangled in the Rolling Shaft of a Crane - Phad, Laxman Gangadhar; Akhade, Swapnil P; Dhawane, S G; Dixit , P G (Journal of Indian Academy of Forensic Medicine, 2015)
Accidental hanging although a rare entity, but occasionally reported in literature. It is very difficult  to differentiate in suicidal and accidental hanging. Circumstantial evidence alone can sufficiently indicate  the accidental nature of occurrence. In the present case a 25 year old male was accidentally hanged  when the shawl wrapped around his neck got entangled in rolling shaft of crane. Initially, he was  completely hanged for some time and then fell on iron rods and bars placed on the ground. He was  immediately shifted in an unconscious condition to Govt. Medical College Nagpur but was declared  brought dead. The Autopsy performed subsequently revealed ligature mark around neck with multiple  injuries on lower limb, un-displaced fracture of thoracic ribs and of thoraco-lumbar vertebrae. This case  reports a rare case of accidental hanging in an adult male, which would have been mistaken to be  homicidal considering the other injuries present on the body.
Keywords: Adult male; Shawl; Accidental hanging; Asphyxia